2007
DOI: 10.1144/sp282.1
|View full text |Cite
|
Sign up to set email alerts
|

Imaging, mapping and modelling continental lithosphere extension and breakup: an introduction

Abstract: AbstactThis Special Publication is a direct outcome of a small but dedicated group of researchers who met in Pontresina, Switzerland, to review and define the fundamental observations characterizing extensional systems and their application in guiding and constraining modelling efforts and results. The various summaries of the keynote addresses give an objective overview of the state of the art in modelling lithospheric extensional systems, both from the regional scale using dynamic models to individual basins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Continental extension is a key result of plate tectonics and leads to rifting and the formation of many of the world's passive margins and ocean basins. Globally rifted margins exhibit a remarkable variation in structural style, including in the width of the domain of thinned continental crust, the degree of asymmetry of conjugate margins, and the amount, type, and spatial and temporal evolution of their sedimentary and magmatic sections [Sengör and Burke, 1978;Royden and Keen, 1980;Steckler et al, 1998;Eldholm et al, 2000;Boillot and Froitzheim, 2001;Davis and Kusznir, 2004;Manatschal, 2004;Geoffroy, 2005;Karner et al, 2007;Van Avendonk et al, 2009;Péron-Pinvidic and Manatschal, 2009]. This range in the style of rifted margins is largely the mechanical consequence of the variability in crustal thickness, lithospheric thermal structure, rheological properties of the crust and mantle, finite strain, and extension rates [England, 1983;Kusznir and Park, 1987;Bassi, 1991Bassi, , 1995Buck, 1991;Buck et al, 1999;Huismans et al, 2005;Lavier and Manatschal, 2006;Gueydan et al, 2008;Huismans and Beaumont, 2011;Brune et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Continental extension is a key result of plate tectonics and leads to rifting and the formation of many of the world's passive margins and ocean basins. Globally rifted margins exhibit a remarkable variation in structural style, including in the width of the domain of thinned continental crust, the degree of asymmetry of conjugate margins, and the amount, type, and spatial and temporal evolution of their sedimentary and magmatic sections [Sengör and Burke, 1978;Royden and Keen, 1980;Steckler et al, 1998;Eldholm et al, 2000;Boillot and Froitzheim, 2001;Davis and Kusznir, 2004;Manatschal, 2004;Geoffroy, 2005;Karner et al, 2007;Van Avendonk et al, 2009;Péron-Pinvidic and Manatschal, 2009]. This range in the style of rifted margins is largely the mechanical consequence of the variability in crustal thickness, lithospheric thermal structure, rheological properties of the crust and mantle, finite strain, and extension rates [England, 1983;Kusznir and Park, 1987;Bassi, 1991Bassi, , 1995Buck, 1991;Buck et al, 1999;Huismans et al, 2005;Lavier and Manatschal, 2006;Gueydan et al, 2008;Huismans and Beaumont, 2011;Brune et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of rifting of continental lithosphere to the point of rupture and seafloor spreading remain some of the more poorly understood aspects of the plate tectonic paradigm [e.g., Karner et al , 2007; Péron‐Pinvidic et al , 2009]. A major impediment has been the limited number of conjugate margin pairs on which high‐quality data are available to allow the empirical testing of numerical models of breakup mechanisms [e.g., Huismans and Beaumont , 2002, 2003; Nagel and Buck , 2004].…”
Section: Introductionmentioning
confidence: 99%
“…A number of possible controls have been suggested to explain observed differences in continental rift style and the varying morphologies of passive margins. The manner and relative significance of how these suggested controls actually impact tectonic processes and passive margin formation are still a subject of ongoing debate (e.g., Armitage et al, 2010;Brune, 2016;Huismans and Beaumont, 2014;Karner et al, 2007;Svartman Dias et al, 2015). Utilizing simplified kinematic models of uniform, instantaneous extension, McKenzie and Bickle (1988) and White and McKenzie (1989) suggested that mantle potential temperature acts as the first-order control on the magnitude of syn-rift volcanism during continental breakup.…”
Section: Potential Influencing Factorsmentioning
confidence: 99%